Prosthetic Knee Septic Arthritis due to Pseudomonas stutzeri - Jihad Bishara; Eyal Robenshtok; Zmira Samra; Silvio Pitlik (Canadian Journal of Infectious Diseases)
Prosthetic joint infection is usually caused by Staphylococcus aureus, coagulase-negative staphylococci and, less commonly, by Gram-negative bacilli and anaerobes. A case of prosthetic joint infection due to Pseudomonas stutzeri in a 73-year-old female with acute promyelocytic leukemia is presented, and the pertinent literature is reviewed. Although the patient had prolonged neutropenia, the infection was successfully treated with antibiotics and without artificial joint replacement.